THE INFLUENCE OF JOB PLACEMENT AND WORK EXPERIENCE ON INCREASING EMPLOYEE PRODUCTIVITY AT THE BRIDA MEDAN OFFICE - Yona Lamtiurna Lase; Savika Amanda; Yana Diana (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
The population for this research was employees at the BRIDA Medan Office. Data collection carried out in this research is: by distributing questionnaires, a data collection technique that is carried out by giving a set of questions or statements to other people who are used as respondents to answer. The author used multiple linear regression analysis techniques, T test, and F test with the help of Statistical Product Service Solution (SPSS Version 23.0) software to process the data first by conducting data tests. Data analysis technique used is multiple linear regression analysis (Multiple Regression) and using test data quality, classical assumptions and hypothesis testing. The analysis showed R Square 0,891 or 89.1%. 829.673 with a confidence level of 5% level test F-account = 829.673> F-table = 2.79 then H0 and H1 accepted, so Job Placement and Work Experience affects simultaneously (simultaneously) on Employee Productivity. While Job Placement with t-count 8.288> t-table 1.676 and significant 0.000 <0.05, then H0 is rejected and H1 accepted and can be interpreted Job Placement partial effect to the Employee Productivity and Work Experience variables with t-count -5.558 < t-table 1.676 and significant 0.000 <0.05, the Work Experience has no effect partially on Employee Productivity, as t-count smaller than the value t-tabel.